Pre-chamber ignition mechanism: Experiments and simulations on turbulent jet flame structure. (15th October 2018) - Allison, P.M.; de Oliveira, M.; Giusti, A.; Mastorakos, E.
Abstract: This work investigates the effects of premixed combustion kinematics in pre-chamber volumes on the development of emitted hot jets from the igniter. The effects of fuel type, orifice diameter, and ignition location are evaluated experimentally, with high-speed OH ∗ and CH ∗ chemiluminescence imaging, and computationally with Large-Eddy Simulations (LES). The imaging experiments allowed for simultaneous viewing of combustion processes within a quartz chamber and of the developing jet flow. Results from these experiments provided insight on the temporal evolution of the jet relative to the growth of an ignited kernel within the chamber, as well as information on the emission or lack of emission of radical species from the chamber. Computational results provided data on the temporal behavior of the pressure within the chamber and profiles of the high velocity flow through the orifice. These results, combined, have shown that dependent on the strain rate and effective orifice size, local quenching of radical species at the orifice occurs which fundamentally change whether hot products, reactive layers, or both are present in the turbulent jet emission. The dynamic structure and composition of the turbulent jet controls its relevance as an effective ignition source.